2010
DOI: 10.1007/s10615-010-0265-6
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in Cross-Cultural Clinical Practice: Narrative Analysis of First Sessions

Abstract: Based on a larger process-outcome study on cross-cultural clinical practice, this report focuses on the client-practitioner engagement process during the first session in cross-cultural therapy. Nine cases with complete pre-and post-treatment measures, process measures, and verbatim session transcripts were selected. The cases represent a wide variety of client-practitioner ethno-cultural differences. The outcome of these cases was determined by a combination of objective and subjective measures. Client-practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 50 publications
1
20
0
3
Order By: Relevance
“…One study by Tsang, Bogo, & Lee (2011) analyzed the session transcript data of nine cases from pre- to post-treatment. Complex coding procedures from a narrative research perspective were supplemented by the information provided on various process and symptom measures (which were both subjective and objective in nature).…”
Section: Empirical Data Identifying Specific Featuresmentioning
confidence: 99%
“…One study by Tsang, Bogo, & Lee (2011) analyzed the session transcript data of nine cases from pre- to post-treatment. Complex coding procedures from a narrative research perspective were supplemented by the information provided on various process and symptom measures (which were both subjective and objective in nature).…”
Section: Empirical Data Identifying Specific Featuresmentioning
confidence: 99%
“…In the face of this intensity, it is tempting for clinicians to withdraw or to emotionally distance themselves as a means of self-protection. However, previous research has demonstrated the value in remaining emotionally attuned and responsive to the client in the midst of powerful, emotional, therapeutic content as opposed to seeking factual information, providing cognitive responses, or asking about behavioral strategies (Tsang, Bogo, & Lee, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Nine clients self-identified as white, two as Asian, and four as African. Of these participants, three were adolescents, six were in their 20s, two in their 30s, three in their 40s, and one in her 50s (see Tsang, Bogo and George, 2003;Tsang, Bogo and Lee, 2011 for details of the original research).…”
Section: Methodsmentioning
confidence: 99%
“…To provide culturally responsive services, several family therapy approaches recommend joining as a means for therapists to convey respect for a family's cultural values and ideas (Greif, 1990;Lee and Horvath, 2014;McGoldrick, 2012;Tsang, Bogo and Lee, 2011). As a way of joining in cross-cultural encounters, some have suggested that therapists need to identify and mobilize parts of themselves that are congruent with the family in order to find common ground (Minuchin and Fishman, 1981).…”
mentioning
confidence: 99%